Solve the given equation for the slope and y-intercept.
2x + 5y + 1 = 0

Question

Asked 10/28/2013 8:42:10 PM

Updated 7/26/2014 9:21:50 AM

1 Answer/Comment

Flagged by yeswey [7/26/2014 9:21:15 AM]

Question

Asked 10/28/2013 8:42:10 PM

Updated 7/26/2014 9:21:50 AM

1 Answer/Comment

Flagged by yeswey [7/26/2014 9:21:15 AM]

Rating

3

2x + 5y + 1 = 0

5y = -2x - 1

y = -2/5x - 1/5 which is the slope intercept form of the line equation.

5y = -2x - 1

y = -2/5x - 1/5 which is the slope intercept form of the line equation.

Added 7/26/2014 9:21:50 AM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [7/26/2014 9:34:17 AM]

The line through (0, -3) and (3, 0)
**Weegy:** 7/5 **User:** Input in standard form the equation of the given line.
The line through (0, -3) and (3, 0)
**User:** 3x - 2y = 6
m =
y-intercept
**Weegy:** The y-intercept of the line whose equation is 3x - 2y = 6 is A.-3
**User:** 3x - 2y = 6
m =
**Weegy:** Input:
lcm(5/3 x^2 y-4/6 x y^3)
Result:
lcm((5 x^2 y)/3-(2 x y^3)/3)
ListPointPlot3D[Table[{x, y, LCM[(x y (5 x - 2 y^2))/3]}, {x, -10, 10}, {y, -10, 10}], [ PlotRange -> All]
Alternate Form:
lcm(1/3 x y (5 x-2 y^2))
] (More)

Question

Not Answered

Updated 4/28/2014 9:40:23 PM

2 Answers/Comments

The line through (0, -3) and (3, 0) in standard form is x - y = 3

Added 4/28/2014 9:37:56 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/28/2014 9:39:36 PM]

3x - 2y = 6

-2y = -3x + 6

y = 3/2x - 3 which is the slope intercept form

so slope m = 3/2, y intercept = -3

-2y = -3x + 6

y = 3/2x - 3 which is the slope intercept form

so slope m = 3/2, y intercept = -3

Added 4/28/2014 9:40:23 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [4/28/2014 9:41:16 PM], Unconfirmed by jeifunk [4/28/2014 9:41:17 PM], Confirmed by jeifunk [4/28/2014 9:41:18 PM]

Find the common solution.
7x + 2y = 4
y = x + 1
**Weegy:** 2x +7y = 5
Just move the second one to the first one and then the answer is that in above. (More)

Question

Not Answered

Updated 5/24/2014 9:45:40 AM

1 Answer/Comment

7x + 2y = 4

y = x + 1

using the second equation to institute y in the first one:

7x + 2(x + 1) = 4

7x + 2x + 2 = 4

9x = 4 - 2

x = 2/9

y = 2/9 + 1 = 2/9 + 9/9 = 11/9

The solution for the system 7x + 2y = 4 y = x + 1 is (2/9, 11/9)

y = x + 1

using the second equation to institute y in the first one:

7x + 2(x + 1) = 4

7x + 2x + 2 = 4

9x = 4 - 2

x = 2/9

y = 2/9 + 1 = 2/9 + 9/9 = 11/9

The solution for the system 7x + 2y = 4 y = x + 1 is (2/9, 11/9)

Added 5/24/2014 9:45:40 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/24/2014 11:57:24 AM]

27,108,387

questions answered

There are no comments.